Global, regional, and national burdens of pancreatic cancer attributable to smoking from 1990 to 2021 and the projections to 2035:a systematic analysis from the global burden of disease study 2021 - Du, Roubing; Wang, Yu; Pan, Mengshu; Zhu, Jie; Zhao, Yaping; Zhang, Chuanzhen; Liu, Changhong; Gao, Yuan (Frontiers in Oncology, 2025)
BackgroundStudies on global epidemiological patterns regarding the burden of pancreatic cancer (PC) attributable to smoking are limited. This study aimed to analyze the latest disease burden of PC attributable to smoking between 1990 and 2021, further analyze the main factors, and predict the trend in the coming period.MethodsData from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 was extracted and analyzed by different geographical levels, age, sex, and socio-demographic index (SDI). Key measures included age-standardized disability-adjusted life years (DALYs) rates (ASDR), age-standardized mortality rates (ASMR), and average annual percentage changes (AAPCs). Further analyses were conducted using the decomposition analysis and Bayesian Age-Period-Cohort (BAPC) model.ResultsGlobally, the ASDR and ASMR of the disease demonstrated a decreasing trend. The burden was significantly higher among males, the middle-aged, and the elderly population. A positive correlation with SDI levels across most regions was exhibited. Join-point analysis indicated a decreasing trend in disease burden among high SDI regions while an increasing trend among low-middle SDI regions. Decomposition analysis indicated that proactive epidemiological changes had played a positive role in reducing the burden in High SDI regions. Projection analysis estimated that the disease burden in East Asia, showing a significant upward trend, warranted particular focus.ConclusionsDespite ongoing tobacco control efforts, the global burden of the disease, which has declined only slightly, remains a significant concern, particularly in high-income areas and among men. Based on stronger tobacco control measures, increased emphasis on disease prevention, early screening, and treatment is essential.